Bureaucracy of The Sambas Sultanate During The Dutch Colonial Period (1818-1942) - Risa, Risa; Sewang, Ahmad M.; Syamsudduha, Syamsudduha; Hasaruddin, Hasaruddin (Jurnal Adabiyah, 2020)
This study aims to describe the enforcement of colonial power in Sambas Sultanate and to analyze the influence of the colonial bureaucratic system on changes in the bureaucratic system in Sambas Sultanate. This study uses a multidisciplinary approach namely the historical approach as the main approach assisted by social science approaches such as sociological, political, anthropological, and economic approaches. The method used is a historical method that includes four steps namely heuristics, verification, interpretation, and historiography. The results showed that the establishment of colonial rule in Sambas Sultanate began with an agreement of friendship and fellowship in 1818, continued with the abolition of the Chinese Kongsis, and prevented the expansion of British power. The implementation of the colonial bureaucracy that had led to modernization then influenced changes in the bureaucratic system in Sambas Sultanate, including changes in the administrative area, the implementation of governance with an ambivalent government system (direct and indirect government systems) and the recruitment of officials adjusted to colonial interest. The ambivalent nature of the bureaucracy aims to maintain the hegemony and position of the Dutch colonial as a superstructure. As a result, there was a patron-client relationship between colonial and traditional governments. تهدف هذه الدراسة إلى وصف تطبيق القوة الاستعمارية في سلطنة سامباس وتحليل تأثير النظام البيروقراطي الاستعماري على التغيرات في النظام البيروقراطي في سلطنة سامباس .تستخدم هذه الدراسة نهجًا متعدد التخصصات هو النهج التاريخي باعتباره النهج الرئيسي الذي تدعمه مناهج العلوم الاجتماعية مثل النهج الاجتماعي والنهج السياسي والنهج الأنثروبولوجي والنهج الاقتصادي .الطريقة المستخدمة هي طريقة تاريخية تتضمن أربع خطوات هي الاستدلال، التحقق، التفسير والتأريخ. أظهرت النتائج أن إقامة الحكم الاستعماري في سلطنة سامباس بدأ بمعاهدة الصداقة والزمالة عام 1818 ، تلاه إلغاء المجتمعات الصينية ومنع توسع السلطة البريطانية. أثر تطبيق البيروقراطية الاستعمارية التي أدت إلى التحديث على التغييرات في النظام البيروقراطي في سلطنة سامباس، بما في ذلك التغييرات في المجال الإداري، وتنفيذ الحكومة بنظام حكومي متناقض (أنظمة حكومية مباشرة وغير مباشرة) وتجنيد المسؤولين الذين تم تعديلهم حسب الأذواق الاستعمارية. تهدف الطبيعة المتناقضة للبيروقراطية إلى الحفاظ على هيمنة ومكان الاستعمار الهولندي كبنية فوقية .ونتيجة لذلك، توجد علاقة راعية-عميل بين الحكومتين الاستعمارية والتقليدية. Penelitian ini bertujuan untuk mendeskripsikan penegakan kekuasaan kolonial di Kesultanan Sambas dan menganalisis pengaruh sistem birokrasi kolonial terhadap perubahan sistem birokrasi di Kesultanan Sambas. Penelitian ini menggunakan pendekatan multidisipliner yaitu pendekatan historis sebagai pendekatan utama dibantu dengan pendekatan ilmu-ilmu sosial seperti pendekatan sosiologis, politik, antropologis dan ekonomi. Metode yang digunakan adalah metode historis mencakup empat langkah yaitu heuristik, verifikasi, interpretasi, dan historiografi. Hasil penelitian menunjukkan bahwa penegakan kekuasaan kolonial di Kesultanan Sambas dimulai dengan perjanjian persahabatan dan persekutuan tahun 1818, dilanjutkan dengan menghapus Kongsi-kongsi Cina dan mencegah perluasan kekuasaan Inggris. Pelaksanaan birokrasi kolonial yang sudah mengarah ke modernisasi kemudian mempengaruhi perubahan sistem birokrasi di Kesultanan Sambas antara lain perubahan wilayah administrasi, pelaksanaan pemerintahan dengan sistem pemerintahan yang bersifat ambivalent (sistem pemerintahan secara langsung dan tidak langsung) dan rekrutmen pejabat disesuaikan selera kolonial. Sifat birokrasi yang ambivalent tersebut bertujuan untuk mempertahankan hegemoni dan kedudukan kolonial Belanda sebagai superstructure. Akibatnya terjalin hubungan patron-client antara pemerintah kolonial dan tradisional.